The Prognosis of Traumatic Small Bowel Injury Accompanied by Liver Injury - Yu Seong Noh; Sung Won Jung; Tae Gil Heo; Pyong Wha Choi; Jae Il Kim; Heung Man Jun; Yong Chan Shin; Sung Min Jung; Eun Hae Um (Journal of Trauma and Injury)
Purpose The aim of this study was to elucidate the prognosis, and other clinical features, such as time to surgery and the amount of transfusion, of small bowel injury (SBI) accompanied by liver injury (LI). Methods We investigated 221 patients with SBI who visited an emergency center from October 2000 to March 2019. We excluded patients with injuries that directly led to mortality, and the remaining 149 patients were divided into the SBI alone (SBI-A) group and the SBI accompanied by LI (SBI-LI) group. Data were collected for preoperative and surgical outcome variables, and the treatment results were compared between groups. Results The SBI-LI group had a higher mortality rate than the SBI-A group (22.4% vs. 14.3%), but this difference was not statistically significant (p=0.061). There were no significant differences between the SBI-A and SBI-LI groups, except for the amount of red blood cell (RBC) transfusion (SBI-A: 3.53±0.1 vs. SBI-LI: 8.38±0.7 packs, p=0.035) and the length of intensive care unit (ICU) stay (SBI-A: 6.7±0.2 vs. SBI-LI: 11.1±0.5 days, p=0.047). Conclusions The SBI-LI group required more RBC transfusions and longer ICU stays than the SBI-A group. SBI accompanied by LI may show higher mortality than SBI alone; however, since the difference was not statistically significant in the present study, larger-scale follow-up research is needed.